2003
DOI: 10.1121/1.1618239
|View full text |Cite|
|
Sign up to set email alerts
|

The dependency of timbre on fundamental frequency

Abstract: The dependency of the timbre of musical sounds on their fundamental frequency (F 0 ) was examined in three experiments. In experiment I subjects compared the timbres of stimuli produced by a set of 12 musical instruments with equal F 0 , duration, and loudness. There were three sessions, each at a different F 0 . In experiment II the same stimuli were rearranged in pairs, each with the same difference in F 0 , and subjects had to ignore the constant difference in pitch. In experiment III, instruments were pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 19 publications
8
103
0
Order By: Relevance
“…These acoustic parameters fall into three broad categories: temporal, spectral, and spectrotemporal descriptors. Consistently across studies, attack time (more precisely its logarithm) and spectral centroid (weighted mean of spectrum energy) have been reported as correlates of timbre space dimensions (see, e.g., Marozeau, de Cheveigné, McAdams, & Winsberg, 2003;Samson, Zatorre, & Ramsay, 1997;McAdams et al, 1995;Krumhansl, 1989;Grey, 1977). Attack time separates impulsive from sustained instruments, and spectral centroid reflects the global spectral distribution.…”
Section: Behavioral Studies Of Timbre Perceptionmentioning
confidence: 78%
See 1 more Smart Citation
“…These acoustic parameters fall into three broad categories: temporal, spectral, and spectrotemporal descriptors. Consistently across studies, attack time (more precisely its logarithm) and spectral centroid (weighted mean of spectrum energy) have been reported as correlates of timbre space dimensions (see, e.g., Marozeau, de Cheveigné, McAdams, & Winsberg, 2003;Samson, Zatorre, & Ramsay, 1997;McAdams et al, 1995;Krumhansl, 1989;Grey, 1977). Attack time separates impulsive from sustained instruments, and spectral centroid reflects the global spectral distribution.…”
Section: Behavioral Studies Of Timbre Perceptionmentioning
confidence: 78%
“…Attack time separates impulsive from sustained instruments, and spectral centroid reflects the global spectral distribution. Other parameters have been less systematically reported: spectrum fine structure (Krimphoff, McAdams, & Winsberg, 1994), spectral spread (Marozeau et al, 2003), or spectral flux (McAdams et al, 1995), the latter being a measure of the variation of the spectrum over time. Altogether, these studies confirm that timbre indeed comprises several perceptual dimensions, with each of these dimensions corresponding to a single acoustic parameter.…”
Section: Behavioral Studies Of Timbre Perceptionmentioning
confidence: 99%
“…Most multidimensional timbre studies consistently find dimensions correlating to brightness (T b ) (Grey, 1977;Marozeau et al, 2003;McAdams et al, 1995;Krimphoff et al, 1994) and often spectral flux is also found as a dimension (Grey, 1977;McAdams et al, 1995). In McAdams et al (1995) and Krimphoff et al (1994), one dimension also corresponds to the attack (characterized by the LRT).…”
Section: A Selection Of Recordings and Timbre Propertiesmentioning
confidence: 99%
“…As timbre is most likely a multidimensional attribute, most studies in timbre rely on a numerical technique known as multidimensional scaling (MDS) [1,[10][11][12][13][14][15]. MDS is a nonlinear data analysis technique which takes known (perceptual) distances between data points and identifies a low dimensional Euclidian space that maintains those distances [16,17].…”
Section: Aural Similaritymentioning
confidence: 99%